Transcriptome analysis of differentially expressed genes in rice seedling leaves under different nitrate treatments on resistance to bacterial leaf blight - Liu, Xintong; Chen, Shunquan; Miao, Changjian; Ye, Huijing; Li, Qingchao; Jiang, Hongzhen; Chen, Jingguang (Frontiers in Plant Science, 2024)
Nitrogen (N), as one of the most abundant mineral elements in rice, not only is the primary limiting factor for rice yield, but also impacts plant disease resistance by modulating plant morphology, regulating biochemical characteristics, as well as enhancing metabolic processes. Bacterial blight, a severe bacterial disease caused by Xanthomonas oryzae pv. oryzae (Xoo), significantly impairing rice yield and quality. Previous studies have shown that moderate application of nitrate nitrogen can improve plant disease resistance. However, further exploration is urgently required to investigate the involvement of the nitrate nitrogen signaling pathway in conferring resistance against bacterial leaf blight. Our research reveals that nitrate nitrogen supply influences rice resistance to bacterial leaf blight. Through transcriptomic profiling of rice leaves inoculated under different nitrate nitrogen concentrations, we identified 4815 differentially expressed genes (DEGs) among four comparison groups, with notable differences in DEG enrichment between low and high nitrate nitrogen conditions, with some members of the NPF family implicated and we preliminarily elucidated the molecular regulatory network in which nitrate nitrogen participates in bacterial leaf blight resistance. Our findings provide a novel insight into a mechanism involving the nitrate nitrogen drive wider defense in rice.